Pemikiran Ekonomi Imam Ibnu Taimiyyah Menguak Pemikiran Ekonomi Muslim Klasik - Marsella Marsella; Mohamad Soleh Nurzaman (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This article aims to analyze classical Muslim economic thought based on the main ideas of Imam Ibn Taimiyah. Authors this article using a qualitative analysis method where the data and information were obtained by conducting a literature search from articles and previous research studies. The results obtained indicate that several principles of Islamic economics were born from the thoughts of Imam Ibn Taimiyah, which must be fulfilled in Islamic economic activities. These principles include monotheism, rules, freedom, justice, balance, and responsibility. Therefore, mus fulfilled all tenets because they are related to one another and cannot be separated. Of course, the thoughts of Imam Ibn Taimiyah have their meaning and purpose in developing economic activities, especially Islamic economics. Artikel ini bertujuan untuk menganalisis pemikiran ekonomi muslim klasik berdasarkan pokok pemikiran Imam Ibn Taimiyah. Dalam penulisan artikel ini menggunakan metode analisis kualitatif dimana data dan informasi yang termuat didalamnya didapat dengan melakukan penelusuran pustaka dari artikel dan kajian penelitian terdahulu. Hasil yang diperoleh menunjukkan bahwa terdapat beberapa prinsip ekonomi islam yang lahir dari pemikiran Imam Ibn Taimiyah yang harus dipenuhi dalam kegiatan perekonomian islam. Prinsip tersebut diantaranya: ketauhidan, kaidah, kebebasan, keadilan, keseimbangan, dan tanggung jawab. Keenam prinsip tersebut harus terpenuhi seluruhnya sebab keenam prinsip memiliki keterkaitan satu sama lain tanpa boleh terpisahkan. Tentunya pemikiran Imam Ibn Taimiyah memiliki makna dan tujuan tersendiri untuk mengembangkan kegiatan perekonomian khususnya ekonomi islam.